AUTOMATION OF DETERMINATION OF RELIABILITY INDICATORS OF CONTROL OBJECTS IN THE PRESENCE OF A ONE-TIME TEAM - Райчев, І. Е.; Харченко, О. Г.; Яцков, М. О.; Василенко, В. А. (Proceedings of National Aviation University (archive), 2021)
The problems of estimating the probability of control objects in the presence of a single command in the control algorithm are considered. Computational algorithms and programs have been constructed, which are further recommended for use during operation, as well as for testing complexes of flight control programs in order to determine the probability of the occurrence of control events.